Nitrogen and phosphorus additions alter soil N transformations in a Metasequoia glyptostroboides plantation - Zhang, Youzheng; Jiang, Pengcheng; Guo, Yaolin; Wu, Ming; Shao, Xuexin; Xu, Hengtao; Wu, Tonggui; Yuan, Wenwen; Li, Niu (Frontiers in Plant Science, 2024)
Nitrogen (N) and phosphorus (P) enrichment due to anthropogenic activities can significantly affect soil N transformations in forest ecosystems. However, the effects of N and P additions on nitrification and denitrification processes in Metasequoia glyptostroboides plantations, and economically important forest type in China, remain poorly understood. This study investigated the responses of soil nitrification and denitrification rates, as well as the abundances of nitrifiers and denitrifiers, to different levels of N and P additions in a 6-year nutrient addition experiment in a M. glyptostroboides plantation. The results showed that moderate N addition (N2 treatment, 2.4 mol•m -2 ) stimulated nitrification rates and abundances of ammonia-oxidizing archaea (AOA) and bacteria (AOB), while excessive N and P additions inhibited denitrification rates and reduced the abundance of nirS-type denitrifiers. Stepwise multiple regression analysis revealed that AOB abundance was the main predictor of nitrification rates under N additions, whereas microbial biomass carbon and nirS gene abundance were the key factors controlling denitrification rates.Under P additions, tree growth parameters (diameter at breast height and crown base height) and AOB abundance were the primary predictors of nitrification and denitrification rates. Our study reveals complex interactions among nutrient inputs, plant growth, soil properties, and microbial communities in regulating soil N transformations in plantation forests. This study also offers valuable insights for formulating effective nutrient management strategies to enhance the growth and health of M. glyptostroboides plantations under scenarios of increasing elevated nutrient deposition.